AN EXAMINATION OF MULTIDIMENSIONAL POVERTY PROFILE IN LIMPOPO, SOUTH AFRICA: IMPLICATIONS FOR THE USE OF CBMS GENERATED DATA FOR INTEGRATED DEVELOPMENT PLANNING. (Proceedings of the International Conference on Social Sciences, 2018)
This study sought to establish the status of multidimensional poverty in Tzaneen Local Municipality in South Africa by using community-based system (CBMS). The objective was to profile multidimensional poverty on basic services and assess the usability of the generated data by local municipalities for Integrated development planning. Consultative, capacity building and CBMS design approach was adopted in the study. Administered household profile questionnaire was used on 1534 households.  Indicators for poverty measurements were generated in partnership with Local municipality and aligned to Statistics South Africa. Data was captured using excel software and imported to CSPro6.3 software for creation of data dictionary and database. Data analysis was done using predetermined indicators and formulas. CBMS-NRDB software was used to generate poverty maps. Community validation approach was used to authenticate study findings. We conclude that CBMS generated multidimensional poverty data and maps can be used for formulating effective Integrated development plans and regular progress monitoring. The information can further be used to assess poverty policy implications at local levels. We recommend that Local municipality use CBMS generated data as a baseline for Integrated development planning and to compliment other national poverty surveys data.
Keywords: Poverty; integrated-development-plans; community based system; South Africa